Relevance theory: pragmatics and cognition - Wearing, Catherine J (Wiley interdisciplinary reviews. Cognitive science, 2015)
Relevance Theory is a cognitively oriented theory of pragmatics, i.e., a theory of language use. It builds on the seminal work of H.P. Grice(1) to develop a pragmatic theory which is at once philosophically sensitive and empirically plausible (in both psychological and evolutionary terms). This entry reviews the central commitments and chief contributions of Relevance Theory, including its Gricean commitment to the centrality of intention-reading and inference in communication; the cognitively grounded notion of relevance which provides the mechanism for explaining pragmatic interpretation as an intention-driven, inferential process; and several key applications of the theory (lexical pragmatics, metaphor and irony, procedural meaning). Relevance Theory is an important contribution to our understanding of the pragmatics of communication.